"Nurses' use of visual management in hospitals—A longitudinal, quantitative study on its implications on systems performance and working conditions". (18th October 2018) - Williamsson, Anna; Dellve, Lotta; Karltun, Anette
Abstract: Aim: The aim of this study was to examine potential benefits provided by daily visual management tool use and explore its association with systems performance and working conditions among hospital nurses. Background: Visual management tools used in everyday work and improvement work in health care theoretically contribute to shared understanding of complex work systems and provide certain user benefits. Cognitive load, miscommunication within and between professional groups, and pressure to engage in care process redesign add to nurses' strained working conditions. Design: Quantitative longitudinal. Methods: Questionnaires were distributed at T0, ( N = 948, 66% response rate), T1 ( N = 900, 70% response rate), and T2 ( N = 621, 72% response rate) to nurses at five hospitals. Three groups of users (daily users, start users, and non‐daily users) were compared by means T1–T2 (significance tested with Wilcoxon signed rank test) and by mixed model repeated measures T0, T1, T2. Results: Daily use associated to better overview of work, collaboration, social capital, and clinical engagement. Job resources were rated higher by daily users. Mental stress increased and development opportunities decreased over time among non‐daily users. There were associations between use and perceptions of systems performance, though the differences between groups were small. Conclusion: This study specifically explores visual management tool use in the hospital setting, which contributes to research by broadening the understanding of cognitive, social, and emotional benefits provided by visual management tool use. Daily use was associated to positive working conditions, small but positive differences in systems performance, and indicated a buffering effect on nurses' mental stress.